Inicjacyjny charakter XI rozdziału Listu do Hebrajczyków - Mateja, Leszek (Vox Patrum, 2018)
The article presents the initiatory nature of the eleventh chapter of the Epistle to Hebrews. The author of the Epistle, on the example of characters from the Old Testament, presents two patterns of faith development: individual and communal. These patterns correspond to the process of the pre-baptism initiation carried out in the ancient Church on three stages: encouragement, precatechumenate and catechumenate. The final extracts of the analysed chapter of the Epistole, interpreted with the use of initiation method, present the faith development of the baptised and their preparation to the martyrdom for faith in Jesus Christ.